2020
DOI: 10.1136/gutjnl-2020-321434
|View full text |Cite
|
Sign up to set email alerts
|

GI symptoms as early signs of COVID-19 in hospitalised Italian patients

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 10 publications
4
29
0
6
Order By: Relevance
“…Surprisingly, intestinal disorders appeared to be correlated with a favorable evolution. This was already suggested in Buscarini's study [20], even though found not significant. Among hematological parameters, low lymphocytes count and high NLR ratio at admission were correlated with a UFE.…”
Section: Discussionmentioning
confidence: 46%
“…Surprisingly, intestinal disorders appeared to be correlated with a favorable evolution. This was already suggested in Buscarini's study [20], even though found not significant. Among hematological parameters, low lymphocytes count and high NLR ratio at admission were correlated with a UFE.…”
Section: Discussionmentioning
confidence: 46%
“… 12 Furthermore, it has been shown that gastrointestinal symptoms can sometimes precede respiratory involvement and be the first manifestation of the infection. 13 These data suggest the possible need to include SARS-CoV-2 infection among the differential diagnosis of acute diarrhea and/or vomiting, at least for the duration of this pandemic.…”
Section: Covid-19 and Gastrointestinal System: Clinical Aspectsmentioning
confidence: 94%
“…In 2020, the sports world was halted by a global pandemic that resulted in a stoppage of most athletic competitions. The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) responsible for the respiratory condition known more commonly as COVID-19 can result in pneumonia-like symptoms and may elicit an inflammatory cascade impacting the bronchioles, alveoli, cardiovascular system, and myocardial tissue (Buscarini et al, 2020 ; Cipollaro et al, 2020 ; Ding et al, 2020 ; Lovato and De Filippis, 2020 ). In March of 2020, the World Health Organization (WHO) classified COVID-19 as a global pandemic (World Health Organization, 2020 ).…”
Section: Introductionmentioning
confidence: 99%